First-principles investigation of Nd(Fe, M)12 (M = K–Br) and Nd(Fe, Cr, Co, Ni, Ge, As)12: Possible enhancers of Curie temperature for NdFe12 magnetic compounds. (March 2022) - Fukazawa, Taro; Akai, Hisazumi; Harashima, Yosuke; Miyake, Takashi
Graphical abstract: Abstract: We investigate the effects of various dopants ( M = K–Br) on the Curie temperature of the magnetic compound NdFe 12 through first-principles calculations. Analysis by the Korringa–Kohn–Rostoker method with the coherent potential approximation reveals that doping the Fe sites with optimal concentrations of Ge and As is a promising strategy for increasing the Curie temperature. To search over a wider space, we also perform Bayesian optimization. Out of over 180, 000 candidate compositions, co-doped systems with Co, Ge, and As are found to have the highest Curie temperatures.